Constitution on Guarantees of Qualified Medical Care - Otamuratov Sadulla; Atamuratova Fеruza Sadullaevna (Scientific Trends, 2024)
This article is dedicated to the constitutional guarantee of the right of citizens to receive qualified medical care, and it shows the importance of the new Constitution of Uzbekistan based on the changes in the right to health care.
Keywords: Constitution, social state, law, New Uzbekistan, medical service, health care, health.